2018
DOI: 10.1038/s41467-018-03588-z
|View full text |Cite
|
Sign up to set email alerts
|

USP52 acts as a deubiquitinase and promotes histone chaperone ASF1A stabilization

Abstract: Histone chaperone ASF1A has been reported to be dysregulated in multiple tumors; however, the underlying molecular mechanism that how the abundance and function of ASF1A are regulated remains unclear. Here we report that ASF1A is physically associated with USP52, which is previously identified as a pseudo-deubiquitinase. Interestingly, we demonstrate that USP52 is a bona fide ubiquitin-specific protease, and USP52 promotes ASF1A deubiquitination and stabilization. USP52-promoted ASF1A stabilization facilitates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 65 publications
3
32
0
Order By: Relevance
“…In addition, a previous study has reported that ASF1A was associated with chromatin higher-order organization and was required for appropriate chromatin assembly [15]. Particularly, ASF1A contributes to tumourigenesis [16], but the functions of ASF1A in colon cancer cells have not been clearly illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a previous study has reported that ASF1A was associated with chromatin higher-order organization and was required for appropriate chromatin assembly [15]. Particularly, ASF1A contributes to tumourigenesis [16], but the functions of ASF1A in colon cancer cells have not been clearly illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…2k, l , WT USP52, but not the USP52 ΔWD40 truncate, successfully rescued DSB resection and HR in USP52-depleted cells, suggesting that the USP52–CtIP interaction is important for the role of USP52 in DSB resection and HR. Because ASF1A is known to be stabilized by USP52 34 , we further investigated whether the effect of USP52 depletion on DSB resection and HR repair is partly due to decreased ASF1A expression. As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…USP52, also named PAN2 (poly(A) nuclease), is a bona fide DUB, which was reported to deubiquitinate and stabilize histone chaperone ASF1A to facilitate chromatin assembly and breast carcinogenesis 34 . Though lacking an active-site cysteine residue, USP52 was able to hydrolyze K6-, K11-, K48-, K63-, and M1-linked ubiquitin chains through its UCH domain 34 . In addition, USP52 has been reported to be a key component of p-bodies which prevents the degradation of HIF1A mRNA and regulates HIF1A-mediated hypoxic response 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FACT binding can destabilize the canonical nucleosomes, disrupting the octamer/DNA contacts, which could result in displacement of H2A/H2B heterodimers (Belotserkovskaya et al, 2003;Chen et al, 2018;McCullough et al, 2011), thereby providing better substrates for Ubp10 ( Figure 2). During nucleosome reorganization induced by FACT, surfaces of H2A/H2B heterodimers that are buried in the context of the nucleosome become more accessible (Kemble et al, 2015) even while the components remained tethered together Xin et al, 2009a;Yang et al, 2018), which could enhance accessibility of H2B-Ub for deubiquitination by Ubp10 even without dimer eviction. We therefore tested the simple model in which binding of DNA to H2A/H2B heterodimers creates a barrier to Ubp10 deubiquitination of H2B-Ub.…”
Section: Fact Stimulates Ubp10 Dub Activity On Nucleosomesmentioning
confidence: 99%